ANALISIS OPEN ORDER DAN CLOSE ORDER TERHADAP MINAT BELI PRODUK ONLINE SHOP STUDI PADA SNJCOLLECTION - Sholihatin Nurul Jannah (Universitas Trunojoyo Madura, 2017)
This research is conducted to understand the effect of Open Order and Close Order on customer buying interest. The more specific objective of this research is to analyze the Open Order and Close Order periods against the buying interest of an Online Shop product on SnjCollection. The research was conducted on 250 consumers as purposive samling, and analyzed using SPSS Version 13 program to see consumer profile, concentration and wariage measure of each indicator of research variables and SmartPLS Version 2.00 for relationship relationship in SEM model. The results obtained, Open Order and Close Order direct relationship with the interest of buying products Online Shop.